Lack of vitamin D signalling in mesenchymal progenitors causes fatty infiltration in muscle - Tohru Hosoyama; Minako Kawai‐Takaishi; Hiroki Iida; Yoko Yamamoto; Yuko Nakamichi; Tsuyoshi Watanabe; Marie Takemura; Shigeaki Kato; Akiyoshi Uezumi; Yasumoto Matsui (Wiley, 2024)
Abstract Background Recent studies have indicated the importance of muscle quality in addition to muscle quantity in sarcopenia pathophysiology. Intramuscular adipose tissue (IMAT), which originates from mesenchymal progenitors (MPs) in adult skeletal muscle, is a key factor affecting muscle quality in older adults, suggesting that controlling IMAT formation is a promising therapeutic strategy for sarcopenia. However, the molecular mechanism underlying IMAT formation in older adults has not been clarified. We recently found that the vitamin D receptor (VDR) is highly expressed in MPs in comparison to myotubes (P = 0.028, N = 3), indicating a potential role of vitamin D signalling in MPs. In this study, we aimed to clarify the role of vitamin D signalling in MP kinetics, with a focus on adipogenesis. Methods MPs isolated from mouse skeletal muscles were subjected to adipogenic differentiation conditions with or without vitamin D (1α,25(OH)2D3, 100 nM) for 7 days, and adipogenicity was evaluated based on adipogenic marker expression. For in vivo analysis, tamoxifen‐inducible MP‐specific VDR‐deficient (VdrMPcKO) mice were newly developed to investigate whether lack of vitamin D signalling in MPs is involved in IMAT formation. To induce muscle atrophy, VdrMPcKO male mice were subjected to tenotomy of the gastrocnemius muscle, and then muscle weight, myofibre cross‐sectional area, adipogenic marker expression, and fatty infiltration into the muscle were evaluated at 3 weeks after operation (N = 3-4). In addition, a vitamin D‐deficient diet was provided to wild‐type male mice (3 and 20 months of age, N = 5) for 3 months to investigate whether vitamin D deficiency causes IMAT formation. Results Vitamin D treatment nearly completely inhibited adipogenesis of MPs through Runx1‐mediated transcriptional modifications of early adipogenic factors such as PPARγ (P = 0.0031) and C/EBPα (P = 0.0027), whereas VDR‐deficient MPs derived from VdrMPcKO mice differentiated into adipocytes even in the presence of vitamin D (P = 0.0044, Oil‐Red O+ area). In consistency with in‐vitro findings, VdrMPcKO mice and mice fed a vitamin D‐deficient diet exhibited fat deposition in atrophied (P = 0.0311) and aged (P = 0.0216) skeletal muscle, respectively. Conclusions Vitamin D signalling is important to prevent fate decision of MPs towards the adipogenic lineage. As vitamin D levels decline with age, our data indicate that decreased vitamin D levels may be one of the causes of IMAT formation in older adults, and vitamin D signalling may be a novel therapeutic target for sarcopenia.